Platelet cothromboplastin: a platelet factor(s) related to the blood clotting mechanisms - Lee, Pyung-Hee; Johnson, Shirley A.; Seegers, Walter H. (Thrombosis and Haemostasis, 1957)
Bovine Platelets contain a factor(s) that greatly enhances the capacity of lung extract thromboplastin to conver purified prothrombin to biothrombin. It also may function with Russell’s viper venom in the activation of prothrombin The activity is destroyed below pH 4 or above pH 11 or at temperatures above 52° C. Concentrates of the activity have been obtained in a fraction of platelets that consists predominately of carbohydrate and protein.